FACTORS AFFECTING THE RELIABILITY OF FINANCIAL REPORTING WAJO THE COUNTY LOCAL GOVERNMENT - Dian Hajra; Jamaluddin Majid (Universitas Muhammadiyah Makassar, 2021)
This study aims to see whether the quality of human resources, the application of accounting standards and information governance affects the financial reporting of local governments in Wajo Regency. The population of this study were all employees of the financial division of the SKPD in the scope of Wajo Regency, namely the Department of Public Works for Spatial Planning and Land, the Office of Health and the Office of Agriculture and Food Security. This type of research is quantitative research. Collecting data from filling out questionnaires. The data collected were processed using SPSS with multiple linear regression analysis to test the hypothesis. Based on the results of research, the government can ignore that the quality of human resources and the application of accounting standards have a positive effect on regional financial reporting. Meanwhile, the use of information technology has no effect on local government financial reporting. This may be due to the fact that the SKPD is lacking in maximizing the integrated computer system.